2013
DOI: 10.1007/s10900-013-9683-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Colorectal Cancer Screening Among Residents of Ohio Appalachia

Abstract: There is an excess burden of colorectal cancer (CRC) in the Appalachian region of the U.S., which could be reduced by increased uptake of CRC screening tests. Thus, we examined correlates of screening among Appalachian residents at average-risk for CRC. Using a population-based sample, we conducted interviews with and obtained medical records of Appalachian Ohio residents 50–75 years between September 2009 and April 2010. Using multivariable logistic regression, we identified correlates of being within CRC scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 51 publications
(54 reference statements)
3
22
0
Order By: Relevance
“…These studies showed that PCP visits [4][5][6][7][8] and physician recommendation were strong predictors of prevalent CRC screening (mostly with colonoscopy). 2,6,8 Our study extends prior work by demonstrating an independent association between prior primary care visits and subsequent Bincident^CRC screening, including outreach screening not linked directly to the primary care visit. This work is particularly important in the modern era, where large private and public health systems have extensive CRC screening outreach programs and are promoting annual FIT/FOBT as a dominant strategy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies showed that PCP visits [4][5][6][7][8] and physician recommendation were strong predictors of prevalent CRC screening (mostly with colonoscopy). 2,6,8 Our study extends prior work by demonstrating an independent association between prior primary care visits and subsequent Bincident^CRC screening, including outreach screening not linked directly to the primary care visit. This work is particularly important in the modern era, where large private and public health systems have extensive CRC screening outreach programs and are promoting annual FIT/FOBT as a dominant strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, patients who are more prevention-oriented may be both more motivated to follow up abnormal screening tests and more engaged in primary care. Previous research in primary care settings 5,6,28 and the general population 4,8 that have examined predictors of CRC screening have focused primarily on Bprevalent^screening (having ever been screened) and in settings where colonoscopy (which offers 10 years of protection) was the predominant screening modality. These studies showed that PCP visits [4][5][6][7][8] and physician recommendation were strong predictors of prevalent CRC screening (mostly with colonoscopy).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39,[56][57] It would be helpful to know whether culturally based education regarding dementia and cognitive screening would increase knowledge, perceptions of risk, and screening behaviors. Engaging experimental research designs to test culturally tailored educational programs based on persons' AD knowledge, beliefs, and perceptions would likely uncover the most effective methods to increase interest in screening.…”
Section: Implications For Researchmentioning
confidence: 99%